PP14 The feasibility and acceptability of a novel low tech intervention to improve pre-hospital data recording for pre-alert and handover to the emergency department. Issue 1 (14th January 2019) - Fitzpatrick, David; Maxwell, Douglas; Craigie, Alan
Abstract : Background: Poor communication during patient handover is recognised internationally as a root cause of a significant proportion of preventable deaths. Data used in handover is not always easily recorded using ambulance based tablets, particularly in time-critical cases. Paramedics have therefore developed pragmatic workarounds (writing on gloves or scrap paper) to record these data. However, such practices can conflict with policy, data recorded can be variable, easily lost and negatively impact on handover quality. Aims: To measure the feasibility and acceptability of a novel, low-tech intervention introduced to support clinical information recording and delivery during pre-alert and handover. The intervention consisted of a reusable card with pre-alert/handover mnemonic and corresponding text boxes for data entry via pen. Methods: A pre and post-test design was used. Paramedics (n=69) based at one city ambulance Station received the intervention. Pre-and post-test measures (12 weeks post-introduction) focussed on paramedic acceptability and utility of intervention, ED staff (n=99) perceptions of handover quality, and proportions of clinical variables documented by ED staff during pre-alert. Results: Twenty-five (36%) paramedics responded to an intervention acceptability questionnaire. Most felt both the pre-alert (n=23 [92%]) and handover (n=18 [72%]) components of the card were ' useful' or 'very useful '. Nineteen (76%) used the card to record clinical information, almost all (n=23 [92%]) felt it ' useful ' to ' very useful ' in supporting pre-alert. Similarly, 65% (n=16) stated they ' often ' or ' always ' used the card during handover. For pre-alert information there were improvements in the provision of 8/11 (72.7%) clinical variables measured. Results from the post-test survey evaluating ED staff (n=37 [37%]) perceptions of handover demonstrated perceived improvements in 3/5 domains measured (p<0.05). Conclusion: This novel low-tech intervention was highly acceptable to paramedic participants, improving their data recording and information exchange processes. Further, well conducted studies are required to test the impact of this intervention on information exchange processes.